2020
DOI: 10.3390/f11111156
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on Carbon Isotope Discrimination from Assimilation to Respiration in a Coniferous and Broad-Leaved Mixed Forest of Northeast China

Abstract: Carbon (C) isotope discrimination during photosynthetic CO2 assimilation has been extensively studied, but the whole process of fractionation from leaf to soil has been less well investigated. In the present study, we investigated the δ13C signature along the C transfer pathway from air to soil in a coniferous and broad-leaved mixed forest in northeast China and examined the relationship between δ13C of respiratory fluxes (leaf, trunk, soil, and the entire ecosystem) and environmental factors over a full growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…4.3. The Agreement Between Δ 13 C TR and Δ 13 C predicted Is Weaker at Four Sites Δ 13 C of structural carbohydrates in wood is closely linked to environmental change, therefore changes in environmental variables could have a greater impact on Δ 13 C TR than on leaf-level Δ 13 C (Diao et al, 2020;Loader et al, 2007). However, this is not consistent with Leppä et al (2022) and Rinne et al (2015) who both found a strong climate signal in leaf-sugar δ 13 C variability.…”
Section: Jules Underestimates the Inter-annual Variability In δ 13 Cmentioning
confidence: 78%
See 2 more Smart Citations
“…4.3. The Agreement Between Δ 13 C TR and Δ 13 C predicted Is Weaker at Four Sites Δ 13 C of structural carbohydrates in wood is closely linked to environmental change, therefore changes in environmental variables could have a greater impact on Δ 13 C TR than on leaf-level Δ 13 C (Diao et al, 2020;Loader et al, 2007). However, this is not consistent with Leppä et al (2022) and Rinne et al (2015) who both found a strong climate signal in leaf-sugar δ 13 C variability.…”
Section: Jules Underestimates the Inter-annual Variability In δ 13 Cmentioning
confidence: 78%
“…Δ 13 C of structural carbohydrates in wood is closely linked to environmental change, therefore changes in environmental variables could have a greater impact on Δ 13 C TR than on leaf‐level Δ 13 C (Diao et al., 2020 ; Loader et al., 2007 ). However, this is not consistent with Leppä et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We put 0.1 to 0.2 mg of the fine powder into a tin capsule for analysis of leaf δ 13 C. We used FlASH 2000 CHNS/O organic elemental analyzer with ConFlo IV, Trace GC ultra and Delta V Advantage stable isotope ratio mass spectrometer for leaf δ 13 C using manufacturers recommended standards. We calculated photosynthetic Carbon Isotope discrimination ∆ 13 C ‰ as done by Körner et al (1988) and Diao et al (2020). Δleaf=δairδleaf1+δleaf1000…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…These species differences can result in pronounced differences in plant carbon gain. Differences in carbon pools and fluxes were investigated by Diao et al [3], in pure conifers vs. mixed broadleaves, through continuous monitoring of CO 2 isotopes in situ. Not just the tree species (or forest type) but also the tree size mattered.…”
mentioning
confidence: 99%